2010
DOI: 10.1111/j.1365-3059.2010.02277.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Eurasian poplar rust to overcome a major quantitative resistance factor

Abstract: The effect of R US , a major quantitative resistance (QR) factor inherited from Populus trichocarpa, was assessed in two Populus deltoides · P. trichocarpa F 1 progenies against eight isolates of Melampsora larici-populina, the causal agent of Eurasian poplar rust. Six isolates were identified on which R US had no significant effect. The first R US -defeating isolate identified suggested a pre-existing potential to overcome R US in the pathogen's populations. The P. deltoides genetic background made no differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…This feature, commonly observed for decades in qualitative resistance (Vanderplank 1975), was more recently described for quantitative resistance (Vale et al 2001) and has been recently fully described for a major quantitative resistance factor in the Melampsora larici-populina/Populus spp. pathosystem (Dowkiw et al 2010). A field experiment with the same studied progeny in the Brazilian state of Bahia would also be essential to provide an explanation for the durability of the resistance of MDF 180.…”
Section: Discussionmentioning
confidence: 98%
“…This feature, commonly observed for decades in qualitative resistance (Vanderplank 1975), was more recently described for quantitative resistance (Vale et al 2001) and has been recently fully described for a major quantitative resistance factor in the Melampsora larici-populina/Populus spp. pathosystem (Dowkiw et al 2010). A field experiment with the same studied progeny in the Brazilian state of Bahia would also be essential to provide an explanation for the durability of the resistance of MDF 180.…”
Section: Discussionmentioning
confidence: 98%
“…R US has been shown to explain up to 80% of the variation for three components of quantitative resistance (latent period, size of uredinia and number of uredinia) after inoculation with seven Mlp strains. Recently, Dowkiw et al (2010) identified several R US -defeating strains which overcame the effect of R US in different poplar genetic backgrounds. The other major locus is inherited from the P. deltoides parent and is associated either by pleiotropy or linkage with the qualitative resistance R 1 .…”
Section: New Phytologist Researchmentioning
confidence: 99%
“…A high degree of synteny exists between the willow and the poplar genomes (Berlin et al 2010), which gives an opportunity to identify candidate genes underlying rust resistance QTLs by utilizing the publicly available Populus genomic resources. In poplar, both qualitative and quantitative M. larici-populina resistance has been described (Lefèvre et al 1994(Lefèvre et al , 1998Dowkiw et al 2003Dowkiw et al , 2010Bastien 2004, 2007;Jorge et al 2005). QTL mapping in a Populus deltoides×Populus trichocarpa family revealed two major and seven smaller resistance QTLs associated to the traits latent period, uredinia number, uredinia size, and field resistance (Jorge et al 2005).…”
Section: Introductionmentioning
confidence: 97%